Common Functions Library - Singh, Jasdeep (My University, 2015)
Every programming language has an in-built function library which provides functions those can be used without being concerned about the internal operations. Similarly “Common Functions Library” also provides such facility to its users. A detailed research work is done in developing this static library. It is a well-structured and well-documented library with integrating similar functions along with their proper description in same files. This project is developed to implement the modular and convenient approach in writing the verification tests for newly designed embedded systems. Deploying CFLib in a centralized database can help the verification engineers to easily understand and use the functions in it. Also, CFLib helps in removing redundancy as multiple copies of the same code will not exist on the centralized database. This project is delivered as a directory containing header files and a library file as an archive file. This archive file was created using “armar” from the object files by compiling the ‘C’ source code using “armcc” and assembly language code using “armasm”.
M.E. (Information Security)
Keywords: Library; functions; Computer Science; Information Security; ARMAR; ARMC